New leadership at the helm of SMU Advisory Board for Real Estate Programme - Singapore Management University (Institutional Knowledge at Singapore Management University, 2021)
Mapletree Investments (“Mapletree” or “the Group”) and Singapore Management University (“SMU”) are pleased to jointly announce new appointment holders of the SMU Advisory Board for the Real Estate Programme, which provides industry insights into evolving industry trends and strategic inputs for SMU’s Real Estate Track including the curriculum and research initiatives. The 11-member Board comprises members who are esteemed leaders in the fields of real estate, tax, investment, finance and law, and have taken on a new three-year term starting from 15 November 2020.